Acute reduction of lower‐body contractile function following a microbiopsy of m. vastus lateralis. (27th September 2018) - Davies, Robert W.; Carson, Brian P.; Bass, Joseph J.; Holohan, Sorcha; Jakeman, Philip M.
Abstract : Twenty‐three resistance trained men 18‐35 years (23 [3] years, 1.8 [0.1] m, 81 [10] kg body mass, 2.3 [1.1] years resistance training experience; mean [SD]) performed repeated maximal voluntary isometric squats (ISQ) and countermovement jumps (CMJ) pre‐ and +30 minutes post a unilateral microbiopsy of m. vastus lateralis . ISQ and CMJ were simultaneously measured by two force plates sampling ipsilateral (biopsied) and contralateral (non‐biopsied) limb force. Bilateral limb force (ipsilateral + contralateral) and imbalance (ipsilateral/bilateral) data are reported as % change from pre‐biopsy (mean [95% CI]). A post‐biopsy reduction in bilateral ISQ peak force (−17 [−23, −11] %; P < 0.001), ISQ rate of force development (RFD; −28 [−41, −15] %, P = 0.002) and CMJ peak take‐off force (−7 [−13, −1]%, P = 0.019) occurred. Imbalance was observed for ISQ peak force (3.2 [2.1, 4.3] %, P < 0.001), RFD (2.8 [1.6, 4.0] %, P < 0.001) and CMJ landing (3.3 [1.0, 5.6] %, P = 0.009), resultant of a force transfer from the ipsilateral (biopsied) to the contralateral (non‐biopsied) limb. These data suggest that in young, resistance trained men a modulatory influence on maximal voluntary static and dynamic lower‐body contractile function is evoked acutely (+30 minutes) following a microbiopsy of m. vastus lateralis .